OPTIMIZING OCCUPATIONAL HEALTH AND SAFETY MANAGEMENT AS A PILLAR OF PRODUCTIVITY AT ELEMENTARY SCHOOL - Imelia Sahda Salsabilla; Yuda Agustian; Wahid, Abdul (STAI Ma'had Aly Al-Hikam Malang, 2025)
Occupational Safety and Health (K3) has an important role in creating a safe and productive work environment at Madrasah Ibtidaiyyah. The implementation of K3 aims to protect educators, students, and staff from the risk of accidents and occupational diseases. This study discusses the implementation of K3 in madrasas, including policies, procedures, and challenges faced in its implementation. Some of the advantages of implementing K3 in madrassas include increasing awareness of safety, reducing the risk of accidents, and increasing comfort in the learning process. However, there are also obstacles such as budget limitations, lack of understanding of educators, and lack of supporting facilities. The results of the study show that the optimal implementation of K3 can increase the effectiveness of learning, create a healthier school environment, and reduce the number of accidents in madrasas. Therefore, support from various parties, including the government, schools, and the community, is needed to increase understanding and procurement of adequate K3 facilities. This study is expected to be the basis for the formulation of K3 policies at Madrasah Ibtidaiyyah to create a safer and conducive learning environment.